Impact of temporal tear meniscus height on the tear osmolarity measurements - Lee, Jaekyoung; Bang, Seung Pil; Kim, Jae-Gon; Jun, Jong Hwa (Scientific reports, 2025)
Tear hyperosmolarity plays a crucial role in initiation of inflammatory response and damage to ocular surface epithelia. Accurate measurement of tear osmolarity is essential for dry eye. This prospective observational and experimental study was conducted in 182 eyes of 182 participants, including 115 subjects with dry eye (Sjögren syndrome aqueous-deficient dry eye [SS ADDE], non-SS ADDE, and evaporative DE [EDE]), 36 with conjunctivochalasis (CCh), and 31 normal controls (NC). The ocular surface disease index (OSDI), tear meniscus height (TMH), Schirmer I test, tear matrix metalloproteinase-9 (MMP-9), tear breakup time, and ocular staining score were assessed. Tear osmolarity was measured using the TearLab osmolarity system (Escondido, CA, USA) by applying 1.0 μl tears collected by micropipette to the TearLab test card or by direct contact between the test card and the temporal tear meniscus. For in vitro analyses, osmolarity of 271.25, 300, 347.5, and 395 mOsm/L solutions were measured at various volumes (0.2, 0.5, 1.0, 2.0, and 5.0 μl) with a TearLab osmometer. Tear osmolarity measured by direct contact was higher than that measured by micropipette (13.7 ± 10.5 mOsm/L, p < 0.001). The difference of osmolarities was higher in the non-SS ADDE, SS ADDE, and CCh than in the NC and EDE ( p < 0.001 for all). Osmolarity was negatively correlated with Schirmer score and TMH (r = − 0.346, p < 0.001; r = − 0.447, p < 0.001, respectively). The smaller the sample volume, the higher the measured osmolarity in the in vitro analysis at 300 and 347.5 mOsm/L (r = − 0.659, p < 0.01; r = − 0.579, p < 0.05, respectively). The TearLab osmometer tended to report higher tear osmolarity inversely proportional to sample volumes, possibly due to the evaporation effect. Therefore, care should be taken when interpreting tear osmolarity in patients with low tear volume or CCh.